Development of Tourism in the Arctic Zone and Its Impact on Environment - BELONOZHKO, Marina L.; BARBAKOV, Oleg M.; ABRAMOVSKY, Anton L. (Journal of Environmental Management and Tourism, 2019)
For a long time, the Arctic was considered a territory not adapted for human life (“dead earth”), impassable either by water or by land due to the climate. Currently, not only scientists, but also ordinary travelers and tourists are going to the North Pole. Today, tourism in the Arctic is one of the rapidly developing areas in the past few years. Therefore, the authors studied the development of tourism in the Arctic and its impact on the environment. It has been established that the development of ecological, cultural, scientific, extreme tourism, sport hunting, fishing and cruises is relevant for the Arctic regions. It was determined that the main problem in the development of tourism in the Russian Arctic is the transport and logistics underdevelopment of the region. But, these territories are so rich in natural, cultural, historical resources that there is the possibility of developing almost all types of tourism.